2016
DOI: 10.1108/mbr-03-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Normative and systems integration in human resource management in Japanese multinational companies

Abstract: Purpose This paper aims to conceptualise a framework of “transnational human resource management” (HRM) and to demonstrate the validity of the model. Design/methodology/approach Evidence is drawn from survey of 93 large Japanese multinational companies (MNCs). Data are analysed through descriptive statistics, hierarchical multiple regression analyses and mediation effect analyses. Findings The analysis reveals that the practices for normative and systems integration are associated with increasing levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 75 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…Likewise, Yu and Meyer-Ohle (2008) revealed that employees who worked for Japanese companies in China had more complaints than those who worked for Western companies, based on interview data. Japanese expatriates also reported particular management and adjustment difficulties in China (Furusawa & Brewster, 2016). These studies indicate that while Japanese expatriates may be able to manage low-skilled workers such as factory workers, they lack the skills to manage highly-skilled employees such as university graduates (Sekiguchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Yu and Meyer-Ohle (2008) revealed that employees who worked for Japanese companies in China had more complaints than those who worked for Western companies, based on interview data. Japanese expatriates also reported particular management and adjustment difficulties in China (Furusawa & Brewster, 2016). These studies indicate that while Japanese expatriates may be able to manage low-skilled workers such as factory workers, they lack the skills to manage highly-skilled employees such as university graduates (Sekiguchi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, local employees in foreign subsidiaries have not been given decision-making authority (Yoshihara, 1996) or promotion opportunities (Legewie, 2002) in Japanese companies. As international HRM for Japanese MNCs has been almost synonymous with the management of Japanese expatriates and host-country nationals have not been treated as potential international managers by the headquarters, the low level of normative integration might have generated mutual distrust between Japanese expatriates and local managers (Furusawa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As far as trust or social capital is concerned, Furusawa, Brewster, and Takashina (2016) use an empirical study of Japanese MNEs to argue that a globally shared corporate philosophy will encourage trust and can act as a "psychological glue" to bind different persons together in a "transnational human resource management" model:…”
Section: Facing These Problems Of Both Expatriation and Localizationmentioning
confidence: 99%
“…For companies having many subsidiaries, normative human resource system ensures a smooth running of the whole corporation, and main leaders shall be fully responsible for the management of these systems [7] . It is necessary to introduce adaptive post evaluation method and construct flexible post management system to achieve adjustable staff managing and improve the vigour of Z Company.…”
Section: Improve the Managing Level Of Leadersmentioning
confidence: 99%